Possibilities for the analysis of Educational Policy from the perspective of Institutions as cognitive and normative frameworks: insights from Sociological Neo-institutionalism (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2025)
This theoretical review article examines in a historical line and from a broad sociological perspective approaches that support and contribute to configure the analysis of policies from the sociological neoinstitutionalism, which conceives Institutions not as political-administrative organs and structures of government but as cognitive and normative frameworks historically configured as social constructs referents of sense. Contributions of referents authors are critically reviewed and a synthesis of the possibilities of sociological neo-institutionalism as an alternative for the analysis of educational policy in the context of Latin America is made. It is oriented towards new researchers interested in entering the Field of Educational Policy Studies from the neoinstitutional perspective with a sociological approach. Keywords: Sociological Neo-institutionalism. Institutions. Cognitive and normative frameworks. Educational policy analysis.